COMPARISON OF THE IMPACT OF THE COVID-19 PANDEMIC AND TECHNOLOGICAL DEVELOPMENTS ON EMISSIONS OF CO2 IN THE AIR TRANSPORT - Čubić, Marija; Török, Adam (Journal of Applied Engineering Science, 2024)
Air transport is a complex and intricate mode of transportation that has both benefits and consequences resulting from the operations of planes. Air travel offers the advantage of saving time during journeys or business visits, but it also has the disadvantage of contributing to carbon dioxide emissions caused by aircraft operations. These emissions present potential risks to both human health and the environment. In order to reduce the negative impacts, new technical advancements can be utilized to limit emissions and, consequently, the discharge of carbon dioxide. The COVID-19 epidemic caused an unprecedented situation where flights were temporarily suspended and aircraft were grounded, leading to a significant decrease in emissions from airline operations. This research utilizes graphical representations to clarify the main factors that lead to reduced carbon dioxide emissions. Moreover, it examines the effects of particular advancements in air transportation and assesses the impact of the pandemic on the overall decrease in emissions.